2007
DOI: 10.1080/13691050601170378
|View full text |Cite
|
Sign up to set email alerts
|

Passionate uprisings: Young people, sexuality and politics in post‐revolutionary Iran

Abstract: This paper examines the sexual and social practices of young people in contemporary Iran. Young people in urban areas live under the rubric of a fundamentalist, Islamist regime which restricts social freedoms such as premarital heterosexual contact, homosexual encounters, dancing, alcohol consumption and large group gatherings. Drawing on close focus research and individual and group inteviews, this paper seeks to analyse young people's responses to these constraints. Findings suggest that many young adults us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…A group of ethnographic studies depict radical changes with regard to sexuality among young people. For instance, an ethnographic study among sexually experienced youth in Tehran showed a dramatic change occurring in the sociosexuality of young people (Mahdavi 2007). Another study emphasised the role of the revolution in creating a crisis of the family in Iran (Khosravi 2007) but disregarded changes that have occurred since the revolution, such as access to global media and the expansion of communication technology.…”
Section: Recent Published Literaturementioning
confidence: 97%
“…A group of ethnographic studies depict radical changes with regard to sexuality among young people. For instance, an ethnographic study among sexually experienced youth in Tehran showed a dramatic change occurring in the sociosexuality of young people (Mahdavi 2007). Another study emphasised the role of the revolution in creating a crisis of the family in Iran (Khosravi 2007) but disregarded changes that have occurred since the revolution, such as access to global media and the expansion of communication technology.…”
Section: Recent Published Literaturementioning
confidence: 97%
“…Factors such as westernization, modernization, education, social networks and worldwide communications, information technology; and a rapidly widening generational gap have created grounds for changes in value systems and norms within this country [37, 51, 56, 62]. …”
Section: Introductionmentioning
confidence: 99%
“…These gaps can allow room for resistance. Pardis Mahdavi explains that even in post-revolution Iran, where the clergy has control of the state and morality police (komiteh) patrol the streets searching for transgressors to arrest, there is a developing-and defiant-subculture of extramarital sexuality among the young (Mahdavi 2007).…”
Section: Regulatory Powermentioning
confidence: 99%